(untitled) (The Gaze: Journal of Tourism and Hospitality, 2022)
Tourism destinations in the world are facing different challenges like natural disasters, conflicts, terrorism, economic crisis, and pandemic affecting the various aspect of international tourism needs. The coronavirus was emerged in Hubai, China at the end of 2019, remained a life-threatening outbreak and a major public health issue. In Nepal, the first case of COVID-19 was seen on January 23, 2020, and as part of the containment strategy suggested by WHO, the Government of Nepal imposed lockdown from March 24, 2020, made policies and regulations to control the national and international border (land & air). The Government also requested its citizens to maintain social distance and restrict the movement of people that has affected the Nepalese tourism sector severely. Chitwan is one of the most important wildlife-based tourism destinations of Nepal after the establishment of Chitwan National Park (CNP) and Sauraha is the main point to enter and visit Chitwan National Park. The tourism sector in Sauraha is also pretentious due to the COVID-19 pandemic. What is the status of tourism in Sauraha before and during the Pandemic? The objective of this study is to know how has COVID-19 impacted on tourism in Sauraha in particular and Chitwan National Park in general. For the research, researchers have adopted a qualitative research approach. Primary and secondary data were collected and interviewed 30 respondents representing various sectors of tourism and hospitality in Sauraha. Findings reveal that the outbreak of pandemic has brought huge negative impact by a rapid shutdown on the tourism industry in Sauraha and this has resulted in the loss of revenue, increase unemployment, frustration, and poverty among local people as well as gave positive things like health awareness, consensus on business, time for training and maintenance of infrastructures, etc.